Türk ceza hukukunda müşterek faillik - Dikmen, Hüseyin (My University, 2020)
Bu tezin konusu olan müşterek faillik, Türk Ceza Kanunu’nun “Faillik” başlığı altındaki37. maddesinde düzenlenmiştir. Buna göre “Suçun kanuni tanımında yer alan fiili birliktegerçekleştiren kişilerden her biri, fail olarak sorumlu olur.”İştirak kavramı, suçun birden fazla kişinin katkısı ile işlenmesini ifade eder. Türk CezaHukukunda iştirak, faillik ve şeriklik olarak ikiye ayrılır. Failin sorumluluğu kendifiilinden kaynaklanmakta iken, şerikin sorumlu tutulabilmesi için bağlılık kuralına ihtiyaçvardır.Faillik; müstakil faillik, dolaylı faillik ve müşterek faillik olarak üç başlık altındaincelenir. Bu çalışma münhasıran müşterek faillik ile ilgili olduğu için iştirak müessesesiile bağlantılı diğer başlıklara ilgisi dâhilinde temas edilmiştir.5237 sayılı TCK’nın iştirake ilişkin düzenlemeleri mülga 765 sayılı kanuna göre farklı veetkin olduğu, ceza sorumluluğunun kapsamını eski kanuna göre genişlettiği için özelliklemüşterek failliğin kapsamı ve sınırı konusunda uygulamada yaşanan tereddütler ortadankaldırılmak istenmiştir.Bu çalışmada öncelikle iştirak kavramı tartışılarak fail ve şerik ayrımı ortaya konulmayave müşterek failin konumu belirlenmeye çalışılmıştır. Daha sonra Türk Ceza Hukuku’ndamüşterek faillik kurumu detaylarıyla incelenmeye çalışılmıştır. Nihayet müşterek faillikdiğer iştirak çeşitleri ile karşılaştırılmış ve böylece inceleme konusu kurumun sınırlarınınbelirlenmesi hedeflenmiştir.

Joint participation, which is the subject of this thesis, is regulated in article 37 of theTurkish Criminal Code under the title of “Perpetration”. Hereunder, “Each one of thepersons who jointly execute the act defined as crime in the law is responsible from itslegal consequences as the offender.”The concept of complicity refers to the crime being committed with the contribution ofmore than one person. Complicity in Turkish Criminal Law is divided into two asperpetration and secondary participation. While the responsibility of the perpetrator arisesfrom his own action, the principle of accessoriness is needed in order to be held theaccomplice responsible.Perpetration is examined under three headings as direct perpetration, indirect perpetrationand joint participation. Since this study is exclusively concerned with joint participation,other topics related to the establishment of complicity have been touched upon if it isrelevance.The regulations of the TCK numbered 5237 regarding complicity are different andeffective than the repealed code numbered 765. It also expanded the scope of criminalliability more than the previous code. Therefore, the hesitations experienced in practiceregarding the scope and limit of joint participation were tried to be removed.In this study, first of all, the concept of complicity is discussed, the distinction betweenthe perpetrator and the secondary perpetrator and the position of the joint participant istried to be determined. Afterwards, the institution of joint participation in TurkishCriminal Law was tried to examine in detail. Finally, the joint participation has comparedwith other types of complicity and thus, it is aimed that the limits of the institution subjectto the investigation were determined.
Keywords: Accomplice; Fail; İştirak; Joint Participant; Kamu hukuku; Müşterek Fail; Perpetrator; Public law; Şerik Complicity